The intelligent library: Thought leaders’ views on the likely impact of artificial intelligence on academic libraries - Cox, Andrew M.; Pinfield, Stephen; Rutter, Sophie (Library hi tech, 2019)
PurposeThe last few years have seen a surge of interest in artificial intelligence (AI). The purpose of this paper is to capture a snapshot of perceptions of the potential impact of AI on academic libraries and to reflect on its implications for library work.Design/methodology/approachThe data for the study were interviews with 33 library directors, library commentators and experts in education and publishing.FindingsInterviewees identified impacts of AI on search and resource discovery, on scholarly publishing and on learning. Challenges included libraries being left outside the focus of development, ethical concerns, intelligibility of decisions and data quality. Some threat to jobs was perceived. A number of potential roles for academic libraries were identified such as data acquisition and curation, AI tool acquisition and infrastructure building, aiding user navigation and data literacy.Originality/valueThis is one of the first papers to examine current expectations around the impact of AI on academic libraries. The authors propose the paradigm of the intelligent library to capture the potential impact of AI for libraries.